Predicting Danger in Immigration Courts. Issue 1 (11th March 2019) - Ryo, Emily
Abstract : Every year, the US government detains thousands of noncitizens in removal proceedings on the basis that they might pose a threat to public safety if released during the pendency of their removal proceedings. Using original audio recording data on immigration bond hearings, this study examines immigration judges' determinations regarding which noncitizens pose a danger to the community. My multivariate analysis that controls for a variety of detainee background characteristics and criminal-conviction-related measures produced three main findings. First, I find that Central Americans are more likely to be deemed dangerous than non-Central Americans. Second, I find that detainees with attorneys are less likely to be deemed dangerous than pro se detainees. Finally, my analysis shows that whereas felony and violent convictions are associated with higher odds of being deemed dangerous, the recency of criminal convictions and the total number of convictions are not predictive of danger determinations. Together, these findings provide new insights into the socio-legal construction of immigrant criminality.